2017
DOI: 10.2147/dddt.s120564
|View full text |Cite
|
Sign up to set email alerts
|

Methanol leaf extract of <em>Actinodaphne sesquipedalis</em> (Lauraceae) enhances gastric defense against ethanol-induced ulcer in rats

Abstract: Actinodaphne sesquipedalis Hook. F. Var. Glabra (Kochummen), also known as “Medang payung” by the Malay people, belongs to the Lauraceae family. In this study, methanol leaf extract of A. sesquipedalis was investigated for their acute toxicity and gastroprotective effects to reduce ulcers in rat stomachs induced by ethanol. The rats were assigned to one of five groups: normal group (group 1), ulcer group (group 2), control positive drug group (group 3) and two experimental groups treated with 150 mg/kg (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Our finding revealed that experimental rats fed with p-Cymene exhibited an increased concentration of PAS staining in stomach sections in comparison to the ulcer control group. Similarly, several investigators using different medicinal plants have reported an increased intensity of PAS staining in stomach sections of experimental rodents [22,56].…”
Section: Discussionmentioning
confidence: 85%
“…Our finding revealed that experimental rats fed with p-Cymene exhibited an increased concentration of PAS staining in stomach sections in comparison to the ulcer control group. Similarly, several investigators using different medicinal plants have reported an increased intensity of PAS staining in stomach sections of experimental rodents [22,56].…”
Section: Discussionmentioning
confidence: 85%
“…[3,28] The stomach mucosa performance barrier does not allow disgrace enzymes, for instance, pepsin effusive stomach wall. [24,29,30] Chiefly, mucus owns real slight permeability large elements, perhaps pepsin, nonetheless closely subjects, alike tension, absolute alcohol increases permeability reason liberation of vasoactive crops, and finally vascular damage. Vascular damaging enhanced alcohol success in gastric tissue and consequence disproportions removal of bicarbonate and building mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Glabra (Kochummen), Lauraceae family, known as "Medang payung", also demonstrated a gastroprotective effect against ethanol-induced ulcers in rats. The extract prevented gastric mucosa disruption by increasing gastric pH and mucus content and decreasing oxidative stress and inflammation, in addition to suppressing apoptosis through the upregulation of HSP-70 and downregulation of Bax protein [50].…”
Section: Gastroprotective Plants With Anti-apoptotic Effectsmentioning
confidence: 98%